2014
DOI: 10.1186/2193-8997-3-8
|View full text |Cite
|
Sign up to set email alerts
|

Retirement intentions in the presence of technological change: theory and evidence from France

Abstract: This paper investigates the role of productivity as a determinant of the worker's retirement intentions. Using an overlapping generation framework, we analyze the retirement decision of a cohort of workers being ability heterogeneous. The labor market is endogenously segmented between workers having the required ability level to occupy jobs where the productivity is indexed to the technological state via on-the-job training (complex jobs) and the rest of workers, who are employed in positions where productivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Second, life-long learning seems important to reduce the cost of training. Hence, sectors with larger technical changes may also be those that offer life-long training to their workers, as in Bartel and Sicherman (1993) and Messe et al (2014). Third, the magnitude of the observed technical change may proxy the underlying nature of different technological or organizational innovations.…”
Section: Main Estimationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, life-long learning seems important to reduce the cost of training. Hence, sectors with larger technical changes may also be those that offer life-long training to their workers, as in Bartel and Sicherman (1993) and Messe et al (2014). Third, the magnitude of the observed technical change may proxy the underlying nature of different technological or organizational innovations.…”
Section: Main Estimationsmentioning
confidence: 99%
“…They use this distinction in their empirical analysis to identify the erosion effect. More recently, Messe et al (2014) use French data to investigate the effect of technical change and on-the-job training on retirement intentions. They find that technical change induces individuals to work longer in jobs with a high probability of skill upgrading.…”
Section: Introductionmentioning
confidence: 99%
“…They find no relationship between job satisfaction and retirement attitude for higher-household income older workers, whereas they find that increases in job satisfaction for low-and mean-household income workers are likely to make the prospect of retirement less attractive. In addition, Messe, Eva, & Wolff (2014) find that older workers who benefit from a skill-upgrading training program have a higher intended retirement age. This study finds that the only attitude towards the workplace that has a significant impact on retirement decisions is a positive attitude towards adapting to a new work environment -the higher the score given for adaptation to new work environment attitude, the higher the propensity to retire early.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 96%
“…This effect is found to dominate the retirement motive from skill obsolescence when technological change is large (Ahituv and Zeira, 2011;Burlon and Vilata-Bufí, 2016). Messe et al (2014) found that technological change induces individuals to work longer in jobs with a higher probability of skill upgrading opportunities, which are associated with frequent on-the-job training. Therefore, the net impact of technological change on early retirement is a priori ambiguous.…”
Section: Technology-induced Early Retirement and Its Interaction With Institutionsmentioning
confidence: 99%